Rotator cuff repair: what questions are patients asking online and where are they getting their answers? - Alexander J. Hodakowski; Johnathon R. McCormick; Dhanur Damodar; Matthew R. Cohn; Kyle D. Carey; Nikhil N. Verma; Gregory Nicholson; Grant E Garrigues (Clinics in Shoulder and Elbow, 2023)
Background This study analyzed questions searched by rotator cuff patients and determined types and quality of websites providing information. Methods Three strings related to rotator cuff repair were explored by Google Search. Result pages were collected under the “People also ask” function for frequent questions and associated webpages. Questions were categorized using Rothwell classification and topical subcategorization. Webpages were evaluated by Journal of the American Medical Association (JAMA) benchmark criteria for source quality. Results One hundred twenty “People also ask” questions were collected with associated webpages. Using the Rothwell classification of questions, queries were organized into fact (41.7%), value (31.7%), and policy (26.7%). The most common webpage categories were academic (28.3%) and medical practice (27.5%). The most common question subcategories were timeline of recovery (21.7%), indications/management (21.7%), and pain (18.3%). Average JAMA score for all 120 webpages was 1.50. Journal articles had the highest average JAMA score (3.77), while commercial websites had the lowest JAMA score (0.91). The most commonly suggested question for rotator cuff repair/surgery was, “Is rotator cuff surgery worth having?,” while the most commonly suggested question for rotator cuff repair pain was, “What happens if a rotator cuff is not repaired?” Conclusions The most commonly asked questions pertaining to rotator cuff repair evaluate management options and relate to timeline of recovery and pain management. Most information is provided by medical practice, academic, and medical information websites, which have highly variable reliability. By understanding questions their patients search online, surgeons can tailor preoperative education to patient concerns and improve postoperative outcomes. Level of evidence IV.